Effects of different inspiratory muscle warm-up loads on mechanical, physiological and muscle oxygenation responses during high-intensity running and recovery - Marostegan, A. B.; Gobatto, C. A.; Rasteiro, F. M.; Hartz, C. S.; Moreno, M. A.; Manchado-Gobatto, F. B. (Scientific Reports, 2022)
Inspiratory muscle warm-up (IMW) has been used as a resource to enhance exercises and sports performance. However, there is a lack of studies in the literature addressing the effects of different IMW loads (especially in combination with a shorter and applicable protocol) on high-intensity running and recovery phase. Thus, this study aimed to investigate the effects of three different IMW loads using a shorter protocol on mechanical, physiological and muscle oxygenation responses during and after high-intensity running exercise. Sixteen physically active men, randomly performed four trials 30 s all-out run, preceded by the shorter IMW protocol (2 × 15 breaths with a 1-min rest interval between sets, accomplished 2 min before the 30 s all-out run). Here, three IMW load conditions were used: 15%, 40%, and 60% of maximal inspiratory pressure (MIP), plus a control session (CON) without the IMW. The force, velocity and running power were measured (1000 Hz). Two near-infrared spectroscopy (NIRS) devices measured (10 Hz) the muscle`s oxygenation responses in biceps brachii (BB) and vastus lateralis (VL). Additionally, heart rate (HR) and blood lactate ([Lac]) were also monitored. IMW loads applied with a shorter protocol promoted a significant increase in mean and minimum running power as well as in peak and minimum force compared to CON. In addition, specific IMW loads led to higher values of peak power, mean velocity (60% of MIP) and mean force (40 and 60% of MIP) in relation to CON. Physiological responses (HR and muscles oxygenation) were not modified by any IMW during exercise, as well as HR and [Lac] in the recovery phase. On the other hand, 40% of MIP presented a higher tissue saturation index (TSI) for BB during recovery phase. In conclusion, the use of different loads of IMW may improve the performance of a physically active individual in a 30 s all-out run, as verified by the increased peak, mean and minimum mechanical values, but not in performance assessed second by second. In addition, 40% of the MIP improves TSI of the BB during the recovery phase, which can indicate greater availability of O2 for lactate clearance.